Quality of care in South Sudan and its associated factors, a facility-based cross-sectional study in public health facilities in Yambio County, Western Equatoria State - Zechariah J. Malel; Garang Dakjur Lueth; Moses Maror Ayuel; Natalia Daniel Singba (BMC Health Services Research)
Abstract Background The patient’s experience of care is critical in determining how satisfied the client is with the quality of health services offered by the health facility. Understanding health needs aids in identifying gaps in service provision as well as potential avenues for planning and improving health care services. The primary goal of this study was to explore the attributes of quality healthcare in South Sudan from the perspective of healthcare recipients. Nonetheless, South Sudan’s health system has remained inadequate since the country’s independence in 2011, with 85% of deliveries performed by unskilled health personnel, high maternal and child death rates, and a lack of vital lifesaving drugs in health facilities. Political unrest, natural disasters, poor infrastructure, and budgetary limits are among the additional factors impeding the provision of high-quality care services to the population in need. However, the South Sudan government, with the support of international health partners, continues to work towards ensuring that basic health needs are met in accordance with SDG-3 recommendations. Method This was a facility-based cross-sectional descriptive study conducted in four selected health facilities in Yambio County, Western Equatoria State, from July 1st to September 30th, 2023. A sample size of 422 was included, and a randomized sampling procedure was used, with 60% of public health facilities supported by non-governmental organizations utilizing the lottery method. Data were collected and entered into SPSS version 25 for descriptive and regression analysis. Results A total of 422 participants were solicited for the study, with a response rate of 99.81 percent. Of the 421 responders, 72% (303/421) were female and 28% (118/421) were male. The overall satisfaction with the experience of quality of health care delivered was 84.8%. A preliminary analysis found that the assumption of multicollinearity was met (Age, sex, feeling of having chance to fully explain a problem to care provider, physical examination, provider’s technical capacity in diagnosis and treatment, provider attitude, client respect) among others, were all associated with the client’s experience of care and satisfaction with the quality of health care. Conclusion The clients who sought health care at the public health facilities in Western Equatorial State were quite satisfied with the quality of health services (84.8%). Provider’s behaviors, attitudes, and technical skills, among other major factors, were found to be associated with the client’s positive experience of care. To uphold health ethics, the study recommends including medical ethics training and client center care into continuing medical educations at health facilities.